On sub-band adaptive chip equalisation for direct sequence code division multiple access downlink over dispersive channels - Ng, Y.H.; Mohamad, H.; Chuah, T.C. (INST ENGINEERING TECHNOLOGY-IET, 2007)
In the downlink of a synchronous direct sequence code division multiple access (DS-CDMA) system utilising orthogonal codes, intersymbol interference (ISI) arises due to multipath propagation, which destroys the code orthogonality and in turn, gives rise to multiple access interference (MAI). Therefore if the ISI can be mitigated through channel equalisation, the MAI can be effectively reduced. However, existing channel equalisers are plagued with different performance and complexity issues. A sub-band adaptive chip equalising (SACE) receiver is proposed as an effective solution for performance enhancement over time-dispersive DS-CDMA downlinks. The SACE receiver exploits the pre-whitening effect of the filter banks to reduce the eigenvalue spread of the input signal covariance matrix. Results based on the popular COST-207 channel models for bad urban and hilly terrain areas are presented with varying loaded conditions. It is observed that in highly dispersive channels, the proposed SACE receiver significantly outperforms the correlation receiver and the full-band equaliser while retaining the desirable attribute of graceful degradation in CDMA networks.